Perspektif Maqashid Syariah Di Era Digital: Membawa Perubahan Radikal Dalam Regulasi Etis Kecerdasan Buatan Di Perbankan Islam - Ahmad Harun Daulay; Mohammad Habibi (Universitas Islam Lamongan, 2026)
Abstract: Artificial intelligence's (AI) quick development has drastically changed the financial services industry, especially Islamic banks. AI implementation creates ethical and regulatory issues, especially with regard to compliance with Islamic legal norms, even while it offers increased efficiency and operational precision. This research examines the evolution of ethical regulation in AI adoption within the Islamic banking sector through a systematic literature review (SLR) of thirty scholarly sources published between 2015 and 2025. The results show that existing regulatory frameworks, especially in areas like algorithmic fairness, data privacy, transparency, and human accountability, are still broad and lack explicit standards in conformity with maqashid shariah. Moreover, sharia supervisory boards' (SSBs') ability to react to new AI technology is still restricted. By suggesting the incorporation of maqashid shariah principles—justice, public benefit, and protection of individual rights—into the ethical governance of AI, this work adds to the expanding conversation on Islamic digital ethics. Practically speaking, the study emphasizes the critical need for cooperative frameworks integrating technologists, Islamic scholars, and regulators to develop AI governance models that are both technologically flexible and compliant with sharia. The study concludes that in order to protect Islamic integrity in the digital age, ethical regulation in Islamic banking needs to go beyond legal formalism and toward a dynamic, value-based methodology.